Identifikasi Faktor Pendukung Pemasaran Berbasis Digital pada Produk Sepatu Lokal - Andri Ikhwana; Husnayanti Husnayanti (Institut Teknologi Garut, 2023)
This local Garut shoe product made from leather has become one of the characteristics and icons of a region faced with competition in the global market. So local products are required to have global competitiveness in order to expand the marketing of local shoe products. The internet will be an opportunity that can be utilized in the marketing process of local shoe products, because the internet can be accessed anytime and anywhere and marketing can be done using various digital media. However, digital marketing cannot be separated from the supporting factors in carrying out digital-based marketing. The aim of this research is to find out the supporting factors for digital-based marketing for local shoe products and find out the development strategies that must be carried out in carrying out this marketing. The research method used was a mix method using multivariate analysis, namely factor analysis by distributing questionnaires to 100 respondents and sampling was taken randomly, then a development strategy was carried out using the Business Model Canvas (BMC) method. The results of this factor analysis are that there are 9 new factors, namely information services, convenience of making transactions, sales promotions, flexibility, attractiveness, quality assurance, services in digital marketing media, price competition strategies and price quality. Recommendations for digital-based marketing development strategies to market local shoe products include adding a website address to the Chanel element, adding information services in the form of links connected to social media in Customer Relationship, adding convenience when making transactions and flexibility in Value Proposition, adding digital media in key activity elements, adding IT experts to Key Resources, adding Internet and brand ambassadors to key partners and adding internet service costs and brand ambassadors to the Cost Structure so that the revenue stream is obtained from sales results from the use of digital marketing media.